2016
DOI: 10.1080/11250003.2016.1222638
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brainstem responses in the Chinese tiger frog Hoplobatrachus chinensis (Osbeck, 1765) (Anura: Dicroglossidae) reveal sexually dimorphic hearing sensitivity

Abstract: Hearing sensitivity affects survival and reproduction in animals that communicate vocally. The Chinese tiger frog exhibits sexual dimorphism in body size, reflecting the evolution of mating behaviour and life-history strategies. In this study, we recorded auditory brainstem responses (ABRs) to determine hearing sensitivity in both female and male frogs. We also compared male and female hearing characteristics with the shape of the tympanic membrane in light of previous studies showing that smaller middle ear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…We found that female and male T. scripta elegans have a similar range of sensitivities (0.2–0.9 kHz), whereas the ABR threshold of females was significantly lower than that in males. These results provide convincing evidence that sexually dimorphic hearing sensitivity has emerged in turtles, and that the hearing of females is more sensitive than that of males, which is consistent with previous findings for frogs and toads (Wang et al 2016, 2019; Yang et al 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that female and male T. scripta elegans have a similar range of sensitivities (0.2–0.9 kHz), whereas the ABR threshold of females was significantly lower than that in males. These results provide convincing evidence that sexually dimorphic hearing sensitivity has emerged in turtles, and that the hearing of females is more sensitive than that of males, which is consistent with previous findings for frogs and toads (Wang et al 2016, 2019; Yang et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…At present, sexual selection (Lovich and Gibbons 1992; Willemsen and Hailey 2003), fecundity effort (Kupfer 2009; Olsson et al 2010), and niche divergence (Thom et al 2010) are the three major hypotheses that have been proposed to explain the evolution and maintenance of sexual size dimorphism (SSD). Although most studies on sexual dimorphism have concentrated on body size or shape, sexually dimorphic hearing sensitivity has also been reported in some species of amphibians (Narins and Capranica 1976; Wang et al 2016, 2019; Yang et al 2018). Remarkably, such sexually dimorphic hearing sensitivity may primarily result from sexual dimorphism of the auditory organs (particularly tympanic membranes) and their physical properties (Dijk et al 2002; Feng et al 2006; Shen et al 2011; Liu et al 2014; Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the biomechanical and electrophysiological frequency tuning with morphological properties along the crista acustica in A. fenestrata, our study provides evidence for an auditory fovea as a sex-specific adaptation that reflects the asymmetric signalling in the reciprocal acoustic communication of these duetting bushcrickets. Sexual dimorphism in hearing organs had been reported predominantly in insects [41][42][43][44][45] and anurans [46][47][48][49][50], but was also shown in geckos [51] and humans [52]. These anatomical differences often reflect sex-specific adaptations of the hearing system to improve the auditory sensitivity or selectivity for acoustic properties of conspecific mating signals or other sounds that have different behavioural relevance to males and females of the same species [23,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Auditory brainstem response (ABR) measurement is a noninvasive and rapid method to measure hearing sensitivity; its use has been validated for frogs [26, 27], toads [28], and reptiles [18, 29]. Our aim was to demonstrate that aging is accompanied by changes in turtle hearing sensitivity by measuring ABR, to assess ontogenetic changes in post-hatchling-to-reproductive T. scripta elegans adults.…”
Section: Introductionmentioning
confidence: 99%